Luhmann Explained : From Souls to Systems. - Moeller, Hans-Georg (Ideas explained series., 2011)
What are systems? What is society? What happens to human beings in a hypermodern world? This book is an introduction to Niklas Luhmann's social system theory which explains specific functions like economy and mass media from a cybernetic perspective. Integrating various schools of thought including sociology, philosophy and biology Luhmann Explained results in an overall analysis of "world society". Special attention is given to the present-day relevance of Luhmann's theory with respect to globalization, electronic mass media, ethics, and new forms of protest.